Birds of the Manembonembo Nature Reserve, North Sulawesi, Indonesia - R F Bororing; I Hunowu; Y Hunowu; E Maneasa; J Mole; M H Nusalawo; F S Talangamin; M F Wangko (KUKILA, 2000)
Manembonembo Nature Reserve in North Sulawesi, Indonesia was established in 1978. To date, virtually no ecological research has been carried out in the reserve. We describe the first systematic survey of birds at Manembonembo. As with many Sulawesi protected areas, this 6,500 ha reserve is relatively small, but in I I days of fieldwork we sighted 72 species of birds. Of particular relevance for conservation is the presence of several threatened species such as Prioniturus flavicans, Megapodius cumingii, and Zoothera erythronota. Manembonembo is seriously threatened by several factors: its small size, hunting, timber collection, and agricultural encroachment.